Genetic and functional characterisation of the LIMD1 promoter and gene product: from lung cancer to the hypoxic response - Foxler, Daniel (2012)
LIM domain containing protein 1 (LIMD1) is a tumour suppressor located at 3p21.3, a region that harbours multiple tumour suppressor genes and is commonly subject to homozygous deletions and loss of heterozygosity in many cancers. The mechanism of LIMD1 tumour suppressive activities are not fully elucidated, however to date it has been shown to bind to the retinoblastoma protein (pRb) and repress E2F driven transcription as well as being a critical component of miRNA mediated gene silencing. Recent work has also identified LIMD1 as a possible negative regulator of hypoxia inducible factor α (HIF1α) and the hypoxic response. In lung cancer, LIMD1 protein expression is down regulated in up to 79% of tumours when compared to normal tissue with gene deletion and loss of heterozygosity accounting for 32 and 12% respectively, leaving 30% of tumours with unexplained mechanism of LIMD1 protein loss.